Reduplication in the First and Third Person Possessor of Lircay - Angaraes Quechua - Escobar Zapata, Emérita (2010)
The central purpose of this research is first to report the existence of the phenomenon of reduplication (FR) in the marks of first and third person possessor /-yniy- / and /-nnin-/ respectively, in the dialect of QuechuaAngaraes Lircay, and according to the classification of Alfredo Torero (1964) falls within one of the groups of the sub-branch II-C. Second, compare the ways propertied that exist in the dialects of Quechua I (QI) and Q II, contemporary with our data, to explain the changes from the protolanguage. Finally, to infer what factors condition the presence of the phenomenon of reduplication in the population object of our study.